Character and Characterization of the Main Characters on Zootopia Movie for Teaching Vocabulary - Lismawati, Agustina; Hidayat, Nur; Setyorini, Ajeng (Jurnal Penelitian Multidisiplin Ilmu, 2024)
The purpose of this study was to find character and characterization, also character’s development to contribution vocabulary mastery in “Zootopia” movie. the writer implemented a descriptive qualitative method to a analyze character, characterization, and character’s development which are supported by theory and various sources literatures and documents. The first purpose of this study was to find character and characterization, while the finding revealed that there are three important character which are Judy, Nick, and Bellwether. Where Judy has respect, responsibility, fairness, tolerance, wisdom, help each other, and confidence. Then Nick has cunning respect, sympathy, support. While Bellwether has manipulative, high IQ, master strategist. The second purpose was to elaborate the character development, where Judy is from coward to brave, underestimated to reliable, weak to strong. Then Nick is from cunning and sly to trustworthy and helpful, while Bellwether is from unappaciated to powerful, and helpful to betrayal. The third purpose was to present that “Zootopia” movie can contributing in vocabulary mastery, especially using movie as teaching material creates fun atmosphere to motivate the student, so they can improve vocabulary learning efficiently. In the end. the writer expected that this study can be reference in vocabulary mastery.